Modelling the impact of intervention measures on total accident cases in Nigeria using Box-Jenkins methodology: A case study of federal road safety commission. Issue 1 (1st January 2017) - Oreko, Benjamin Ufuoma; Nwobi-Okoye, Chukwuemeka Chidozie; Okiy, Stanley; Igboanugo, Anthony Clement
Abstract: Road traffic accidents (RTA) have been a very big problem in many developing countries including Nigeria, causing many deaths and disabilities. The aim of this research is to model the effects of intervention measures adopted by the Nigerian government in curbing RTA. In the research road traffic accident data from 1960 to 2014 were analyzed using Box-Jenkins intervention methodology. The result of the modeling and analysis showed that the establishment of Federal Road Safety Commission in 1987, a Nigerian Government intervention measure, had an abrupt temporary impact on RTA in Nigeria ( ω 0  = −2, 423). The findings also showed that the total number of accident cases in Nigeria from 1961 to 1987 (26 years), the period before the intervention, was 657, 280 while the total number of accident cases from 1988 to 2014 (26 years), the period after the intervention, was 430, 721. This represents a 34.5% reduction in total accident cases after the intervention. In terms of accident density there was a 67.4% reduction in accident density during the post intervention period under consideration. It can be concluded that the establishment of the road safety agency has a positive impact on total cases of RTA in Nigeria by reducing it significantly, although RTA still continues to be a big problem in Nigeria. This model and analysis will assist road safety agencies to re-strategize in their policy implementation in order to further reduce RTA occurrence, the number of persons killed and injured in Nigeria.